Comprehensive Insulation Design Method of High Voltage Oil-Immersed Pulse Transformers - Spyridon Stathis; Bastian Korthauer; Florian Krismer; Jurgen Biela (IEEE Access)
This article proposes a detailed method for the design of the insulation distances in high voltage (HV) oil-immersed pulse transformers, named the stressed oil volume scaling (SOVS) method. The developed SOVS method uses breakdown measurement data, which are obtained from a scaled down measurement setup (SDMS) by applying pulsed voltages of different pulse durations in the range of a few $μ $ s. The acquired breakdown measurement data are scaled to the pulse transformer, offering a methodical approach for estimating the pulse breakdown voltage with a defined probability of breakdown for the pulse transformer. The proposed SOVS method shows a significantly lower computational effort compared to the typical insulation design approaches for pulse transformers, and it is possible to be integrated within a general design procedure of oil-immersed HV pulse transformers. As an example, the method is applied to the specifications of the cyclotron autoresonance maser (CARM) pulse transformer, which is currently under investigation at the ENEA research center. Further, the method is applied to two already built pulse transformers in order to evaluate its efficacy.